Characteristics of pendent heliconia for use in landscape and as cut flower - Loges, Vivian; Castro, Carlos Eduardo Ferreira de; Castro, Ana Cecília Ribeiro de; Gonçalves, Charleston (Ornamental Horticulture, 2016)
The Heliconia species with pendent inflorescences and colorful bracts is a good option for landscaping in tropical gardens and cut flowers market. In Brazil only a few species of Heliconia are commercially produced eg. H. rostrata, H. rauliniana and H. chartacea. Aiming to increase the use of outstanding native plants and the knowledge of these products for enthusiasts of tropical flowers, this work was carried out to characterize H. chartacea, H. collinsiana, H. magnifica, H. pendula, H. platystachys, H. pogonantha, H. rostrata, H. rauliniana and H. vellerigera for use in landscaping and as cut flower. The evaluations were performed on plants belonging to the Germplasm Collection of the Instituto Agronômico (IAC), in Ubatuba Unit of Research and Development, located in Ubatuba, São Paulo State, growing in partial shade conditions. Qualitative and quantitative characteristics related to clump and flower stem aspects were analyzed. A point scoring system was used to determine the species most suitable as landscape plant or as cut flower. The plant height range from 2.3 (H. rostrata) to 7.0 m (H. pogonantha), having inflorescence with vibrant and different colors, varying between yellow, orange, red, pink, green and two color combinations. The inflorescences from most of the species were visible in the clump and remain in good conditions for two (H. platystachys) to five months (H. magnifica, H. rostrata and H. pogonantha) and present six (H. platystachys and H. pendula) to 40 (H. pogonantha) open bracts. White wax in leaves or inflorescences were observed in H. collinsiana, H. chartacea, H. pendula and H. platystachys. On the other hand, H. magnifica, H. rostrata, H. pogonantha and H. vellerigera exhibit a hairy surface, pubescent to lanuginose. The postharvest durability longer than 10 days was observed only in H. platystachys, H. rostrata, H. chartacea, and H. rauliniana. This characterization and scoring system were important to indicate and diversify heliconia use for landscaping and cut flower.